Effect of sucrose preculture and culture inoculum density on cryopreservation of olive somatic embryos - Bradaï, Fatiha; Almagro-Bastante, Javier; Sánchez-Romero, Carolina (Elsevier, 2023)
This study reports improvement of a protocol for cryopreservation of olive somatic embryos by using the droplet-vitrification method on aluminum foil strips. Two different approaches were considered in order to optimize cryopreservation: investigating the effect of somatic embryos growth conditions, specifically, the influence of the inoculum density of suspension cultures from which cryopreservation explants were collected, and studying the impact of preculture with different sucrose concentrations in both solid and liquid medium. The results obtained showed a significant effect of inoculum density on cryopreservation evaluated as regrowth rate, although a significant influence on recovery percentage could not be inferred. Sucrose preculture significantly improved recovery rates after cryopreservation. The best results were achieved with somatic embryos previously incubated in liquid ECO medium supplemented with 0.2 M sucrose for 28 days. After this treatment, 90% of explants resumed embryogenesis 12 weeks after thawing. Preculture in liquid medium containing 0.2 M sucrose also had a significant influence on the initial response after cryopreservation, with first signs of regrowth resumption 3 days after thawing, compared to 24-25 days in control, non-precultured embryos. Surviving explants continued actively growing, exhibiting the growth pattern normally observed in olive. As revealed by the histological analysis, cell proliferation greatly increased in somatic embryos precultured on sucrose-enriched media. Cellular features of meristematic and proembryogenic cells, mostly constituting the proliferative regions, make them more prone to survive cryopreservation, thus explaining higher recovery rates found after these treatments.
Keywords: Crioconservación; Anatomía vegetal; Olivo-Embriones; Aceitunas; Olivos; Embriogénesis somática; Cryopreservation; Histological analysis; Inoculum density; Olive; Somatic embryos; Sucrose preculture